La agresividad infantil y su incidencia en el proceso enseñanza aprendizaje de los niños y niñas de 3 a 6 años de edad de la Unidad Educativa Dr. Alfredo Pareja Diezcanseco, de la ciudad de Machala parroquia Jambelí cantón Machala año lectivo 2012-2013. - Fernández Santos, Lorgia Esperanza (2015)
They are different situations that have been woven around childhood aggression, but among them can present environment where the student lives, education of parents etc. All these factors influence children to be replicated within the educational environment, aggressive behavior is one of the main complaints of parents and educators regarding children, turning frequently, often faced with aggressive, manipulative or unruly children but we do not really know how to act with them and how we can influence their behavior to reach change.